2014
DOI: 10.1021/ef502369e
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Gas Hydrate Formation Probability Distributions on Quasi-free Water Droplets

Abstract: We systematically studied the formation probability distributions of methane−propane (C 1 /C 3 ) mixed gas hydrates on a quasi-free water droplet as a function of the mixed gas pressure of up to 14 MPa. It was found that the maximum achievable subcooling temperature (ΔT) distributions of C 1 /C 3 mixed gas hydrates on a quasi-free water droplet were significantly greater than those on a water sample contained in a glass sample cell, for all of the mixed gas pressures studied. The most probable subcooling was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…It is not possible to repeat the measurement of a particular nucleation event and produce a standard deviation from the resulting ensemble, because each nucleation event is stochastic (i.e., not repeatable). In our previous studies, we showed the whole range of nucleation probability distribution in the form of “stochasticity bars”. ,, A “stochasticity bar” is not a traditional error bar or standard deviation of a Gaussian distribution but includes both the ubiquitous random error and the genuine stochasticity that is unique to nucleation phenomena. In the current study, however, the “net amount” of the memory effect is defined as the most probable difference between two probability distributions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not possible to repeat the measurement of a particular nucleation event and produce a standard deviation from the resulting ensemble, because each nucleation event is stochastic (i.e., not repeatable). In our previous studies, we showed the whole range of nucleation probability distribution in the form of “stochasticity bars”. ,, A “stochasticity bar” is not a traditional error bar or standard deviation of a Gaussian distribution but includes both the ubiquitous random error and the genuine stochasticity that is unique to nucleation phenomena. In the current study, however, the “net amount” of the memory effect is defined as the most probable difference between two probability distributions.…”
Section: Resultsmentioning
confidence: 99%
“…We have been developing a class of high pressure automated lag time apparatus (HP-ALTA) over the last several years. HP-ALTA can repeatedly apply hundreds of linear cooling ramps to a small volume of sample water under an isobaric condition of up to 15 MPa and record the maximum achievable subcooling for each cooling ramp. Because of the extremely long induction times involved in the nucleation phenomena of gas hydrates at shallow subcoolings, a systematic study of induction time distributions at constant subcoolings has not been feasible without introduction of an arbitrary cutoff maximum waiting time. , Instead, we select an approach to use the maximum achievable subcooling distributions as a measure of nucleation probability distributions of gas hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…This may not be surprising given that the heterogeneous nucleation rate of gas hydrates was measured only very recently in the absence of a solid wall. 8,29,30 In the present study, we investigated the nucleation rates of natural gas hydrates in the absence of a solid wall (with the use of a quasi-free water droplet suspended in squalane) and compared the results to those in the presence of a solid wall to assess the impact of a solid wall on the memory effect. It was found that the memory effect was not detected in the quasi-free water droplet, which supported the idea that the presence of a solid wall is required for the manifestation of the memory effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…No attempt has hitherto been made to investigate the memory effect in the absence of a solid wall, even though its presence has been invoked as a possible cause of the memory effect. This may not be surprising given that the heterogeneous nucleation rate of gas hydrates was measured only very recently in the absence of a solid wall. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Distribution functions for accessible supercooling in hydrate nucleation (methane, a mixture of methane and propane) on the surface of water were studied by Maeda et al [20] . The studies were continued in the works dealing with heterogeneous nucleation of hydrates on quasi-free water drops, for the purpose of obtaining an empirical description of the regularities under investigation [21,22] . The effect of the type of hydrate-forming agent on hydrate nucleation was studied [23] .…”
Section: Introductionmentioning
confidence: 99%